Murine IL-10 gene transfer inhibits established collagen-induced arthritis and reduces adenovirus-mediated inflammatory responses in mouse liver. - Quattrocchi, E; Dallman, M; Dhillon, A; Quaglia, A; Bagnato, G; Feldmann, M (2001)
The effects of homologous IL-10 administration during an established autoimmune disease are controversial, given its reported immunostimulatory and immunosuppressive properties. Studies of collagen-induced arthritis have shown efficacy with repeated administrations of IL-10; however, when the EBV IL-10 homologue was administered via adenovirus gene transfer technology the results were equivocal. Therefore, the present study was undertaken to elucidate the effects of prolonged homologous IL-10 administration via adenovirus-mediated gene delivery on the progression of established arthritis. Collagen type II (CII)-immunized mice received i.v. injections of 10(7) or 10(8) PFU of an E1-deleted adenoviral vector containing the murine IL-10 gene (AdIL-10), after arthritis onset. Mice were monitored for 3 wk for disease progression, and gene transduction was assessed by quantification of serum mIL-10. CII-specific cell-mediated and humoral immune responses were analyzed by lymph node cell proliferation, cytokine production, and anti-CII Ab responses. Furthermore, because adenoviral vectors have been reported to induce organ dysfunction due to cell-mediated immune responses to the viral Ags, we have also evaluated delayed-type hypersensitivity responses and reactive hepatitis to the systemically delivered adenovirus and whether the IL-10 produced could influence those responses. Sustained suppression of autoimmune arthritis and elevated serum levels of IL-10 were achieved in our study. AdIL-10 treatment reduced cell-mediated immune reactivity, but did not affect humoral responses. Furthermore, IL-10 was able to reduce, but not totally abrogate, adenovirus-induced hepatic inflammation. These findings provide further insights into the diverse interplay of immune processes involved in autoimmune inflammation and the mechanism of cytokine immunotherapy.